2022
DOI: 10.18502/jabs.v11i3.8789
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Troxerutin on Apelin-13 and Its Receptor Gene Expression in Ovarian of Pregnant Rats Fed a High-Fat Diet

Abstract: Background & Objective: Apelin is a newly discovered member of adipocytokines that acts as an endogenous ligand for the G-coupled receptor for the protein orphan (APJ). This study aimed at investigating the beneficial effect of troxerutin (TRO) on apelin-13 and its receptor mRNA expression in the ovary of high-fat diet (HFD) fed rats. Materials & Methods: 40 three-week old female Wistar rats received control diet (CD) or HFD for 8 weeks. After mating, pregnant animals were divided into 4 subgroup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…functions in normal and pathological conditions in humans and animal models. Int J Mol Sci (2019) 20 (18):4431. doi: 10.3390/ijms20184431…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…functions in normal and pathological conditions in humans and animal models. Int J Mol Sci (2019) 20 (18):4431. doi: 10.3390/ijms20184431…”
Section: Discussionmentioning
confidence: 99%
“…Maternal nutrition during pregnancy can lead to growth abnormalities and reproductive dysfunctions (32). Our previous study revealed that maternal HFD during pregnancy and lactation markedly decreased the number of primary, secondary, and graafian follicles, while increasing the number of atretic follicles in their offspring (18). HFD has also been shown to increase atretic follicles through upregulation of ovarian cell cycle inhibitors, expansion of granulosa cells (Gc) apoptosis (33), or modifications of the expression of genes engaged in growth, development, and apoptosis of follicles in the ovary (34).…”
Section: Obesity and The Reproductive Systemmentioning
confidence: 99%
See 3 more Smart Citations